Diving Response in Rats: Role of the Subthalamic Vasodilator Area - Golanov, Eugene V.; Shiflett, James M.; Britz, Gavin W. (Frontiers in Neurology, 2016)
Diving response is a powerful integrative response targeted toward survival of the hypoxic/anoxic conditions. Being present in all animals and humans it allows to survive adverse conditions like diving. Earlier we discovered that forehead stimulation affords neuroprotective effect decreasing infarction volume triggered by permanent occlusion of the middle cerebral artery in rats. We hypothesized that cold stimulation of the forehead induces diving response in rats, which, in turn, exerts neuroprotection. We compared autonomic (AP, HR, CBF) and EEG responses to the known diving response-triggering stimulus, ammonia stimulation of the nasal mucosa, cold stimulation of the forehead, and cold stimulation of the glabrous skin of the tail base in anesthetized rats. Responses in AP, HR, CBF and EEG to cold stimulation of the forehead and ammonia vapors instillation into the nasal cavity were comparable and differed significantly from responses to the cold stimulation of the tail base. Excitotoxic lesion of the subthalamic vasodilator area, which is known to participate in CBF regulation and to afford neuroprotection upon excitation, failed to affect autonomic components of the diving response evoked by forehead cold stimulation or nasal mucosa ammonia stimulation. We conclude that cold stimulation of the forehead triggers physiological response comparable to the response evoked by ammonia vapor instillation into the nasal cavity, which considered as stimulus triggering protective diving response. These observations may explain the neuroprotective effect of the forehead stimulation. Data demonstrate that subthalamic vasodilator area does not directly participate in the autonomic adjustments accompanying diving response, however, it is involved in diving-evoked modulation of EEG. We suggest that forehead stimulation can be employed as a stimulus capable of triggering oxygen-conserving diving response and can be used for neuroprotective therapy.